The effect of canning process on textural properties, sensorial attributes and bioactive content of non-melting peach cultivars - Christofi, Marina (Department of Agricultural Science, Biotechnology and Food Science, Faculty of Geotechnical Science and Environmental Managment, Cyprus University of Technology, 2021)
Peach (Prunus persica (L.) Batsch) belongs to the Rosaceae family and Amygdyloideae subfamily, grouped under the Prunus genus with origin from the Asian continent. It is one of the most important temperate fruit crops worldwide in terms of production volumes. A significant portion of peach fruits are being processed and are being offered as canning product throughout the year. Canned peach fruit is an added-value product, attractive to a different target market than the fresh fruit and facilitate year-round availability. Peach canning industry largely expands its finished products in the global market, having important economic implications for the main peach producing countries. Despite the great economic importance, a limited number of studies have dealt with the assessment of textural properties, compositional and sensorial perception as well as the nutritional profile of peaches destined for canning process. Fruit of eight clingstone non-melting peach cultivars (cvs. ‘Romea’, ‘Catherina’, ‘Mirel®’, ‘Fercluse®’, ‘Andross’, ‘Everts’, ‘Ferlate®’, ‘VLG’) with scalar on-tree ripening, spanning from beginning of July to mid of September, was used as study material for the needs of the current dissertation. Fruits were harvested at commercially maturity stage based on destructive and non-destructive indicators and qualitative attributes, including flesh colour, flesh firmness, soluble solids content and titratable acidity of fresh produce, were determined. Subsequently, lots of fruit with similar maturity indices per cultivar were processed at two filling mediums; the standard (LS, light syrup) and a low-calorie filling medium (GJ, grape juice syrup) to fit with current consumer-market trends. Canned peaches were assessed for their qualitative and textural attributes. The latter were assessed with the employment of a multipurpose texture analyzer through application of three large deformation assays (Puncture, Texture Profile Analysis, Kramer shearing). Individual organic acids and sugars in the fresh and canned fruit were quantified using liquid chromatography. Sensory quality attributes of canned products were evaluated through the establishment of a customized quantitative descriptive analysis. Total phenolics, total carotenoids and individual bioactive compounds (both in fresh and canned forms) were determined with the employment of UV-vis spectrophotometer and LC-MS/MS, respectively. The abovementioned protocols were employed in three interrelated, yet complementary, research works. Initially, the aim of the first technical study was dual and included the setting up of a list of sensorial descriptors and the elaboration of an analytical toolkit to evaluate the textural properties of canned peaches using large deformation mechanical analysis. Thereafter, the effect of canning process on compositional, sensorial and textural attributes of fruit of an array of non-melting peach cultivars, packed in LS and GJ syrup was assessed. Such analyses were conducted after 6 and 24 months post-canning. Subsequently, the phytochemical content (carotenoids and phenolic compounds) of the examined cultivars was determined in order to assess the effect of both the genotype and the canning process on the bioactive content of peach fruit. The objective of the initial study dealt with the setting up of a list of sensorial descriptors and the elaboration of a toolkit to evaluate the textural properties of canned peaches using large deformation mechanical testing. To this aim, a standardized vocabulary (“consensus language”) was initially developed towards the determination and quantification of 15 sensorial attributes through a quantitative descriptive analysis (QDA) approach. Textural properties were additionally evaluated with a TA-XT Plus texture analyzer by applying three discrete large deformation tests [(a) puncture test with a flat cylindrical probe; (b) texture profile analysis (TPA) with a flat compression plunger; and (c) Kramer shear test (KST) cell with a bladed fixture]; that is a total of nine textural properties, namely, “puncture firmness” (individual halves), “Kramer” hardness (applied in a complex mixture of peach slices), “TPA” hardness (central section of halves), fracturability, consistency, cohesiveness, springiness, chewiness, and total hardness. The established protocols, providing complementary information, are readily applicable to the canning industry in setting up qualitative tests to determine product shelf life as well as to assist on going breeding programs for the evaluation of new candidate clingstone cultivars. Subsequently, the above-mentioned protocols were employed in an array of non-melting peach cultivars. Descriptive quantitative analysis indicated discrete varietal differences, providing useful insights for the industry regarding the quality and marketing potential for canned products of each cultivar. Fruit packed in diluted clarified grape juice concentrate, aiming towards a less caloric content product, demonstrated an inferior consumer perception regarding bitterness, astringency and off-taste. Storage of the canned fruit (6 versus 24 months) led to texture depletion modifications on a cultivar-dependent manner. ‘Ferlate®’ registered desirable textural properties, while ‘Mirel®’, besides the appealing orange-coloured fruit pieces, aligned with satisfactory sensorial properties, provide further marketing options for the peach canning industry. Both early (‘Romea’) and late season ripening (‘VLG’) cultivars were proven amenable to canning with acceptable quality attributes, offering a sustainable solution towards extension of the non-melting peach harvesting season. However, their qualitative attributes were inferior of the rest examined cultivars and new genotypes with early or late ripening can be exploited towards the extension of the peach canning campaign. Lastly, the effect of genotype and canning process on bioactive content was determined. Data showed that the individually quantified phytochemicals as identified in fresh fruit, differ significantly among the examined cultivars. Notably, the widely grown ‘Andross’ cultivar demonstrated the highest contents. In terms of phytochemical profile upon canning, the use of grape juice as filling medium, a liquid matrix higher in bioactive content compared to sugar syrup, resulted in reduction of the degradation of bioactive compounds, possibly by balancing out diffusion processes between fruit tissue and packing medium. In addition, grape juice also supplies a good source of polyphenols while this is not the case for the sugar-based standard syrup. Overall, the canning process differentially affected individual carotenoids and phenolic compounds. Peach carotenoids and α-tocopherol with the exemption of β-carotene were more stable than phenolic compounds upon thermal treatment and subsequent storage. The sum of zeaxanthin and lutein remained unaffected by the caning process compared to β-carotene. All soluble phenolic compounds, including neochlorogenic acid, chlorogenic acid, procyanidin B1 and catechin, showed a dramatic decrease after the canning process. Oligomeric and polymeric proanthocyanidins, which are relevant phenolics in peach, were not studied in the present project as they were not extracted with the solvents used. Overall, the unique cellular matrix of each cultivar seems to modulate the degree of loss of bioactive compounds as well as the cellular degradation of the fruit tissues and thereby affecting the diffusion of biochemical components into the liquid media, thus rendering certain cultivars and packing liquids more appropriate for canning. Results reported herein shed light on largely unexplored areas of research dealing with the canning industry. The established protocols that can be used for determination of sensorial and textural properties of canned peach products can be exploited both by the industry to evaluate a given product and additionally provides to breeders an excellent tool to select new advanced clingstone peach cultivars, amenable to canning with superior properties. Moreover, the proposed analytical toolkit would be valuable to establish appropriate thermal processing protocols aiming at desirable end-product quality characteristics as well as to monitor the shelf life of these processed fruit products. From the nutritional standpoint, the unique cellular matrix of individual peach fruit cultivars seems to modulate the degree of loss of bioactive compounds during the canning process. The present study was focused on those phenolic that could be absorbed in the small intestine and therefore can have direct systemic effects. The analysis of oligomeric and polymeric proanthocyanidins, which are relevant phenolics in peach, should be considered as a future perspective, as they interact with gut microbiota and are relevant (poly)phenols regarding health-promoting effects.
Keywords: Prunus persica; Clingstone; Texture; Aroma; Firmness; Fruit processing; Quantitative descriptive analysis; Sensory evaluation; Texture profile analysis; Phenolics; Carotenoids; Nutrition; Canning